Bringing nutritional ketosis to the table as an option for healing the pediatric brain - Gertler, Tracy S.; Blackford, Robyn (Frontiers in Nutrition, 2024)
Our core premise is that personalized variations of a ketogenic diet are likely to benefit pediatric patients with neuropsychiatric symptoms across multiple domains. Although pediatric epilepsy is currently a well-accepted indication for a strict ketogenic diet, there is a dearth of knowledge and therefore clinical guidelines upon which to recommend nutritional ketosis for pervasive pediatric conditions such as autism spectrum disorder and ADHD, even when comorbid epilepsy is present. However, there are published cohort studies and current clinical trials implementing medical ketogenic therapies for cognitive impairment, psychiatric comorbidities, motor disability, and even neuroinflammation. As holistic practitioners, it is imperative that we consider the health of a child in its entirety -and additionally offer the ketogenic diet as a therapeutic option when it may be synergistic in treating extra-neurologic diseases such as obesity. As there are uniquely pediatric potential adverse side effects such as linear growth deceleration and micronutrient deficiencies, previous trials in epilepsy and our center's experience have already proven the ketogenic diet to be a low-risk intervention when optimized with appropriate patient monitoring and support.